Adipose tissue inflammation and metabolic dysfunction: a clinical perspective - Tam, Charmaine S. (Horm Mol Biol Clin Investig, 2013)
Obesity is characterized by a state of chronic low-grade inflammation due to increased immune cells, specifically infiltrated macrophages into adipose tissue, which in turn secrete a range of proinflammatory mediators. This nonselective low-grade inflammation of adipose tissue is systemic in nature and can impair insulin signaling pathways, thus, increasing the risk of developing insulin resistance and type 2 diabetes. The aim of this review is to provide an update on clinical studies examining the role of adipose tissue in the development of obesity-associated complications in humans. We will discuss adipose tissue inflammation during different scenarios of energy imbalance and metabolic dysfunction including obesity and overfeeding, weight loss by calorie restriction or bariatric surgery, and conditions of insulin resistance (diabetes, polycystic ovarian syndrome).